2011
DOI: 10.5012/jkcs.2011.55.6.940
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Four Component Reaction of Unsymmetrical 1-Methylbarbituric Acid with BrCN and Various Aldehydes in the Presence of Et3N and/or Pyridine

Abstract: ABSTRACT. Reaction of 1-methylpyrimidine-(1H,3H,5H)-2,4,6-trione (1-MBA 1) as an unsymmetrical barbituric acid with cyanogen bromide and various aldehydes in the presence of triethylamine and/or pyridine afforded diastereomeric mixtures of new class of heterocyclic stable 5-aryl-1,1'-dimethyl-and 5-aryl-3,1'-dimethyl-1H,1'H-spiro[furo[2,3-d]pyrimidine-6,5'-pyrimidine]2,2',4,4',6'(3H,3'H,5H)-pentaones which are dimeric forms of 1-methyl barbiturate at the range of 0 o C to room temperature. In the reaction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The structures of salts 4a '– 4b ' are shown in Figure . According to our previous reported mechanisms for the formation of the salts 10 and 11 , a representative proposed reaction mechanism for the formation of salt 4a ' is shown in Scheme . The salt of 7a ' was formed in the presence of Et 3 N and in the absence of BrCN (path b ).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of salts 4a '– 4b ' are shown in Figure . According to our previous reported mechanisms for the formation of the salts 10 and 11 , a representative proposed reaction mechanism for the formation of salt 4a ' is shown in Scheme . The salt of 7a ' was formed in the presence of Et 3 N and in the absence of BrCN (path b ).…”
Section: Resultsmentioning
confidence: 99%
“…18,20,21,23 The structures of 13a¢-e¢ have also been reported by the same authors. [18][19][20][21]23 In these types of reactions in the presence of BrCN, the only exception of b-dicarbonyl compounds for cyclopropanation (C-attack) are the malononitrile 26 and Meldrum's acid 27 under the same condition. The novelty and advantagues of the present research work is the selective formation of sole spiro dihydrofuran from among of four possible products (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…16 Yan et al reported the synthesis of spiro dihydrofurans using DABCO catalysis. 17 Recently we have reported the one-pot reaction of an aldehyde with a cyclic b-dicarbonyl compound in the presence of cyanogen bromide (BrCN) and triethylamine [18][19][20][21] and L-(+)-tartaric acid (TA). 22 The one-pot reaction of aromatic dialdehydes with (thio)barbituric acids in the presence of BrCN and triethylamine have been reported by our research group.…”
Section: Introductionmentioning
confidence: 99%
“…4‐Hydroxybenzaldehyde and 2‐pyridinecarbaldehyde yield exclusively one diastereomer under the same condition. Aldehydes possessing strong electron‐donor were produced exclusively by two geometric isomers of Knoevenagel adduct ( E ‐ and Z ‐isomers) [58].…”
Section: Synthesis Of Spiro[furo[23‐d]‐pyrimidinesmentioning
confidence: 99%